2021
DOI: 10.3233/jad-200971
|View full text |Cite
|
Sign up to set email alerts
|

The Retinal Vessel Density Can Reflect Cognitive Function in Patients with Alzheimer’s Disease: Evidence from Optical Coherence Tomography Angiography

Abstract: Background: There is increasing evidence that Alzheimer’s disease (AD) patients may present decreased cerebral blood perfusion before pathological brain changes. Using the retina as a window to the brain, we can study disorders of the central nervous system through the eyes. Objective: This study aimed to investigate differences in retinal structure and vessel density (VD) between patients with mild AD and healthy controls (HCs). Furthermore, we explored the relationship between retinal VD and cognitive functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 44 publications
1
33
0
Order By: Relevance
“…Another three studies were excluded because of lack of sufficient data for analysis after full-text checking of the remaining 11 studies. Eight cross-sectional OCTA studies on the retinal changes among AD, OCTAMCI patients, and HC were included in this meta-analysis [ 2 , 6 , 17 20 , 30 , 31 ]. Studies published between January 1st 2015 and March 31st 2021 were covered.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another three studies were excluded because of lack of sufficient data for analysis after full-text checking of the remaining 11 studies. Eight cross-sectional OCTA studies on the retinal changes among AD, OCTAMCI patients, and HC were included in this meta-analysis [ 2 , 6 , 17 20 , 30 , 31 ]. Studies published between January 1st 2015 and March 31st 2021 were covered.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies using Optovue offered measurements of VD for the SCP and DCP and FAZ area between the AD patients and HC. Wang et al (2021) [ 19 ] and Yan et al (2021) [ 20 ] did not find evidence of a difference in SCP, DCP and FAZ area between AD and HCs. Wu et al (2020) [ 2 ] found a change in DCP and FAZ but no change in SCP between AD patients and HCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether there are retinal microvasculature alterations in patients with AD is yet to be fully determined. Several studies using OCTA have reported significantly decreased vascular density in the eyes of patients with AD compared to controls (Jiang et al, 2018 ; Wang et al, 2021 ), and this change was positively associated with cognitive dysfunction (Yan et al, 2021 ). In contrast, another study revealed that there were no significant differences in the retinal vascular density between patients with AD and controls (Querques et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have highlighted impairments of flow, as measured by either flow density or vessel density, of the SVP, a network of vessels that branch off of the central retinal artery [ 97 ] and supply the innermost layers of the retina, such as the rNFL and inner ganglion cell layer, in AD and cognitively impaired patients [ 95, 98–100 ]. A recent study by Yan et al compared 37 patients with AD to 29 age matched controls and found a positive correlation between retinal vascular density and reduced rNFL thickness, measured by OCTA, in patients with mild AD [ 101 ]. Another study by Chua et al found significantly reduced macular vessel density in both the SVP and DVP in patients with AD, while those with MCI showed reduction in the SVP only [ 102 ].…”
Section: Noninvasive Imaging Of the Retinamentioning
confidence: 99%